2013
DOI: 10.1021/np400224w
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Suppresses the Differentiation of THP-1 Cells through the Inhibition of NOX2 mRNA Expression and the Membrane Translocation of p47phox

Abstract: Luteolin (1), a natural product occurring in many vegetables and fruits, is known to have several biological activities. Cluster for differentiation (CD) families, such as CD11b, -14, and -36, are expressed during pathological processes of atherosclerosis and are used broadly as markers of monocytic differentiation into macrophages. Herein, it was investigated whether 1 and three other flavonoids [chrysin (2), apigenin (3), and tricetin (4)] blocked 12-O-tetradecanoylphorbol 13-acetate (TPA)-triggered inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…These results are consistent with our previous findings, in which luteolin exhibited potent radical scavenger activity and significantly suppressed monocytic differentiation into macrophages. 25) These results indicate that luteolin maintains good redox homeostasis, particularly in extracellular spaces.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These results are consistent with our previous findings, in which luteolin exhibited potent radical scavenger activity and significantly suppressed monocytic differentiation into macrophages. 25) These results indicate that luteolin maintains good redox homeostasis, particularly in extracellular spaces.…”
Section: Discussionmentioning
confidence: 88%
“…Luteolin functions as an inhibitor of TPA-induced monocytic differentiation 25) and oxidized low-density lipoprotein-elicited EC-SOD decreases in human vascular smooth cells. 51) In the present study, we tested whether some flavonoids suppress CoCl 2 -elicited decreases in EC-SOD, and found that luteolin exerted a potent inhibitory effect against this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B). We previously reported that luteolin suppressed monocytic THP‐1 differentiation [Makino et al, ]. Therefore, the effects of luteolin on oxLDL‐elicited reductions in EC‐SOD expression were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…(34,35) It has been reported that CAPE is decomposed into caffeic acid and phenethyl alcohol by intracellular esterase, and caffeic acid with catechol skeleton possess anti-oxidative properties. (8,36) We recently reported that a treatment with CAPE suppressed monocyte adhesion to endothelial cells by inhibiting the accumulation of intracellular ROS.…”
Section: Discussionmentioning
confidence: 99%